B-spline solution of non-linear singular boundary value problems arising in physiology - Çağlar, Hikmet; Çağlar, Nazan; Özer, Mehmet (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2009)
We use B-spline functions to develop a numerical method for computing approximations to the solution of non-linear singular boundary value problems associated with physiology science. The original differential equation is modified at singular point then the boundary value problem is treated by Using B-spline approximation. The numerical method is tested for its efficiency by considering three model problems from physiology. (C) 2007 Elsevier Ltd. All rights reserved
Keywords: Oxygen-Uptake Kinetics; Spherical Cell; Diffusion-Problems; Numerical-Solution; Finite-Difference; Cubic Spline; Human Head; Oksijen Alım Kinetiği; Küresel Hücre; Difüzyon Sorunlar; Sayısal Çözüm; Sonlu Farklar; Kübik Spline; İnsan Naşı